Literature Review: Water Spinach Variety KK-09 for Irrigation Optimization in Dry Land - Mushthofa; Suripin; Dyah Ari Wulandari (Jurnal Penelitian Pendidikan IPA, 2025)
The increasing need for food due to population growth demands the optimization of dry land through efficient irrigation strategies. One approach is the selection of alternative crops with low water requirements but high economic value. This study aims to assess the potential of the KK-09 water spinach variety as an alternative cropping pattern in optimizing dry land irrigation. The method used is a literature review based on the Scopus database with relevant keyword searches and topic mapping using the Vos viewer tool. A total of 70 articles related to irrigation optimization in dryland were identified. In addition, an analysis of water requirements was conducted based on plant growth phases (germination, vegetative, flowering, and ripening). The results show that KK-09 water spinach only requires ± 720 mm of water in one planting cycle (110 days), with an average discharge requirement of ± 0.069 liters/second/hectare. The economic water efficiency reaches IDR 68/mm and a profit of IDR 100,400/m³, making it superior to other secondary crops such as corn, sorghum, and mung beans. These findings indicate that the KK-09 variety has the potential to be a sustainable irrigation solution for areas with limited water availability.